Loss on ignition, water content, and pH measurements in surface sediments (2019-2020) within DynaCom experimental islands and saltmarsh enclosed plots at different elevation levels, Spiekeroog, Germany - Daniela Pieck; Claudia Thölen; Isabell Hentschel; Helmut Hillebrand; Michael Kleyer; Kertu Lõhmus; Oliver Zielinski (PANGAEA, 2021)
Data presented here were collected between Januar 2019 to November 2020 within the research unit DynaCom (Spatial community ecology in highly dynamic landscapes: From island biogeography to metaecosystems, https://uol.de/dynacom/) of the Universities of Oldenburg, Göttingen, and Münster, the iDiv Leipzig and the Nationalpark Niedersächsisches Wattenmeer. Experimental islands and saltmarsh enclosed plots were created in the back barrier tidal flat and in the saltmarsh zone of the island of Spiekeroog. Sediment samples for the determination of pH, water content and loss on ignition were taken bi-/monthly in surface sediments (0-3 cm depth). Samples were measured in the laboratory within two months after sampling. Further data sets will be uploaded regularly.